Germination capacity and temperature dependence in Mediterranean species of the Balearic Islands - Galmes, J.=700 1 Medrano, H; Flexas, J.
(En, Es)
ilus., 54 ref.
Keywords: GERMINACION; ORGANISMOS INDIGENOS; TEMPERATURA; ESPAÑA; ISLAS BALEARES